Influence of electrically neutral nickel atoms on electrical and recombination parameters of silicon - Bakhadyrkhanov, M.K.; Ismaylov, B.K.; Tachilin, S.A.; Ismailov, K.A.; Zikrillaev, N.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
The results of this study show that the creation of clusters from impurity nickel atoms almost completely suppresses the generation of thermal donors within the temperature range 450 to 1200 °C. The composition of these clusters was determined using the technique of energy dispersive X-ray spectroscopy, which revealed that the typical cluster consists of silicon atoms (65%), nickel atoms (15%), and oxygen atoms (19%). Based on the experimental results, the authors have suggested that the nickel atoms intensively perform the role of getter for oxygen atoms in the course of clusterization. It was shown that the additional doping of silicon with nickel at T = 1100…1200 °C enables ensuring a sufficiently high thermal stability of its electrical parameters within a wide temperature range. За результатами цього дослідження показано, що створення кластерів з домішкових атомів нікелю майже повністю пригнічує генерацію теплових донорів у діапазоні температур 450–1200 °C. Склад цих кластерів визначали за допомогою методу енергетично-дисперсійної рентгенівської спектроскопії. Виявлено, що типовий кластер складається з атомів кремнію (65%), нікелю (15%) та кисню (19%). На основі експериментальних результатів автори припустили, що атоми нікелю інтенсивно виконують роль геттера для атомів кисню в процесі кластеризації. Показано, що додаткове легування кремнію нікелем при Т = 1100–1200 °C дозволяє забезпечити досить високу термостабільність його електричних параметрів у широкому діапазоні температур.